Evaluation of ResistancePlus MG FleXible, a 'near-patient' test for the detection of Mycoplasma genitalium and macrolide resistance mutations, using freshly collected clinical samples. Issue 1 (23rd January 2021) - Murray, Gerald L.; Doyle, Michelle; Bodiyabadu, Kaveesha; Vodstrcil, Lenka A.; Garland, Suzanne M.; Danielewski, Jennifer; Machalek, Dorothy A.; McGuinness, Colette; Plummer, Erica L.; De Petra, Vesna; Williamson, Deborah A.; Bradshaw, Catriona S.
Abstract : Introduction. Mycoplasma genitalium is a sexually transmitted pathogen with increasing resistance to first- and second-line antimicrobials. The 'near-patient test' ResistancePlus MG FleXible (SpeeDx) detects M. genitalium plus four macrolide resistance mutations (MRMs), facilitating same-day patient follow up. Hypothesis/Gap Statement. This assay has not been assessed on freshly collected samples. Aim. Our goal was to evaluate the performance of the ResistancePlus MG FleXible test against the standard of care open platform test. Methods. ResistancePlus MG FleXible (analysed on the Cepheid GeneXpert platform) was evaluated on freshly collected samples and compared to the standard of care open platform test ResistancePlus MG (SpeeDx) analysed on the LightCycler 480 II (Roche). Results. For 270 valid tests, ResistancePlus MG FleXible yielded a high positive per cent agreement (PPA) of 94.1% [96/102; 95 % confidence interval (CI): 87.6–97.8 %] and negative per cent agreement (NPA) of 95.2% (160/168; 95 % CI: 90.8–97.9%) for M. genitalium detection compared to the reference assay (kappa for test concordance of 0.89; 95 % CI: 0.83–0.95). Performance was similar across different sample types. For the detection of MRMs, ResistancePlus MG FleXible had a PPA of 97.1% (66/68; 95% CI: 89.8–99.6) and NPA of 78.6% (22/28; 95 % CI: 59.0–91.7), with test comparison kappa of 0.79 (95 % CI: 0.65–0.93). Notably, of six discordant results (i.e. determined to be wild type by the reference assay), five were positive for MRMs by Sanger sequencing, indicating that the ResistancePlus MG FleXible assay has an improved performance for mutation detection. Conclusion. ResistancePlus MG FleXible had comparable test performance for M. genitalium detection as the open platform assay, with improved detection of MRMs. The ResistancePlus MG FleXible 'near-patient' assay can deliver a rapid result to expedite appropriate treatment.